Elementary algebraic geometry - Kendig, Keith (Dover Publications, 2015)
"This second edition of an introductory text is intended for advanced undergraduate and graduate students who have taken a one-year course in algebra and are familiar with complex analysis. Concrete examples and exercises illuminate chapters on curves, ring theory, arbitrary dimension, and other topics. Includes numerous updated figures specially redrawn for this edition. 2014 edition"--